Some psychological aspects in speech and hearing problems - AD, Bhavani (Journal of All India Institute of Speech and Hearing, 1972)
Many Psychological factors are found to be associated with Speech and Hearing Problems. They need a detailed study, so that the problems can be understood and therapeutic programmes can be outlined effectively. Many persons with such problems may not be able to come to the clinic. All the factors that contribute towards such problems are not known. Survey and screening programmes would be helpful to discover some of these cases. One such screening was undertaken at Davanagere, when our staff camped there for three days